Determining the Levels of How Families Shape Children's Engagement with Science: A Scale Development Study - Bal, Emine; Kaya, Gökhan (Afyon Kocatepe University, 2022)
This study aims to develop a scale that can be used to determine the levels of how families shape children’s engagement with science. The study was conducted in the basic research design. The data collection was carried out in two stages. In the first stage, the data obtained from the scale applied to 324 people were subjected to exploratory factor analysis. In the second stage, data from 181 people were used for confirmatory factor analysis. As a result of the EFA, it was found that the factor loads ranged from .521 to .893, the Kaiser-Meyer-Olkin value was .866, the total variance explained was 62.254%, and the Cronbach’s alpha value was .907. As a result of the CFA, however, it was found that the X2/df value was 2, and the RMSEA value was .079. Thus, a 5-point, 3-factor Likert type scale, consisting of 18 items, was obtained with validity and reliability according to the analysis results. The factors involved in the scale were called “Practical Applications (Activities and Experiments)”, “Introduction to Science” and “Building Scientific Foundations”. With the developed scale, it is believed that researchers in the field can determine the level of orientation of children of families with different demographics and children of different age groups to science. Bu çalışmanın amacı, ailelerin çocuklarını bilime yönlendirme düzeylerini belirlemek için kullanılabilecek bir ölçek geliştirmektir. Çalışma temel araştırma niteliğinde yürütülmüştür. Amaç doğrultusunda ilk olarak ilgili alan yazın taranarak madde havuzu oluşturulmuştur. Oluşturulan madde havuzu uzman görüşüne sunulmuş ve daha sonra ölçeğin pilot uygulaması yapılmıştır. Uygulama kapsamında toplam 505 ebeveyn araştırmanın çalışma grubunu oluşturmuştur. Uygulama iki aşamada yürütülmüştür. Birinci aşamada 324 kişiye uygulanan ölçekten elde edilen veriler açımlayıcı faktör analizine tabi tutulmuştur. İkinci aşamada ise 181 kişiye uygulanan ölçekten elde edilen veriler doğrulayıcı faktör analizi için kullanılmıştır. Açımlayıcı faktör analizi sonucu faktör yüklerinin .521 ile .893 arasında değiştiği, Kaiser-Meyer-Olkin değerinin .866, açıklanan toplam varyansın %62.254 ve Cronbach’s Alpha değerinin ise .907 olduğu bulunmuştur. Doğrulayıcı faktör analizi sonucu ise X2/Sd değerinin 2 olduğu, RMSEA değerinin .079 olduğu bulunmuştur. Yapılan araştırma doğrultusunda elde edilen verilerin analiz sonuçlarına göre araştırmacılar tarafından geçerliği ve güvenirliği sağlanmış 18 maddeden oluşan 5’li likert tipinde 3 faktörlü bir ölçek elde edilmiştir. Ölçekte yer alan faktörler “Pratik Uygulamalar (Etkinlik ve Deney)”, “Bilimle Tanıştırma” ve “Bilimsel Temel Oluşturma” olarak adlandırılmıştır. Geliştirilen ölçek ile alandaki araştırmacıların, farklı demografik özelliklere sahip ve farklı yaş gruplarında çocuğu olan ailelerin çocuklarını bilime yönlendirme düzeylerini belirleyebileceği düşünülmektedir.
Keywords: Bilim; Family Science; Bilime Teşvik; Science; Aile Bilimi; Family Orientation; Engagement With Science; Aile Yönlendirmesi